Effect of Thought Stopping and Five-Finger Therapy in Reducing Anxiety Among Breast Cancer Patients’ Families at Mamajang Health Center (International Forum of Researchers and Lecturers, 2025)
Breast cancer remains one of the most common malignancies affecting women worldwide, with consequences that extend beyond the physical burden of illness to also encompass psychological distress for both patients and their families. Family members, particularly women who often take the primary caregiving role, are vulnerable to heightened levels of anxiety due to the emotional strain and responsibilities of caring for loved ones undergoing cancer treatment. Elevated anxiety may hinder their capacity to provide optimal support and lower their overall well-being. In response, various non-pharmacological interventions have been developed to help reduce such distress. This study sought to evaluate the effectiveness of a combined therapeutic approach, namely Thought Stopping and Five-Finger Hypnotherapy, in alleviating anxiety among family members of breast cancer patients at Mamajang Public Health Center in Makassar City. Employing a quasi-experimental design with a pre-post test framework, the research involved 120 female participants identified as experiencing mild to moderate anxiety. Anxiety levels were assessed using the Zung Self-Rating Anxiety Scale (ZSAS) before and after the intervention, which consisted of three structured sessions, each lasting approximately 30 minutes. Data analysis through the Wilcoxon Signed Rank Test revealed that 75% of respondents showed a reduction in anxiety, shifting from moderate to mild categories. The mean rank scores dropped notably from 92.3 prior to the intervention to 40 after the sessions. Statistical analysis confirmed the intervention’s effectiveness, yielding a significant p-value of 0.000 (p < 0.05). The findings strongly suggest that Thought Stopping combined with Five-Finger Hypnotherapy represents an accessible, cost-effective, and practical non-pharmacological option for reducing anxiety in caregiving families. This approach holds promise for integration into primary healthcare services, offering families sustainable strategies to cope with emotional challenges associated with breast cancer care.